Taking a Step Further in Identifying Ideal Blood Pressure Range Among Hemodialysis Patients: A Systematic Review and a Meta-Analysis - Aftab, Raja Ahsan; Sellappans, Renukha; Ming, Cheong Kah; Shaik, Imam (Frontiers in Pharmacology, 2020)
Abstract Background Hypertension is one of the primary predictor of mortality among end-stage renal disease (ESRD) patients on dialysis. However, there is no consensus on an ideal blood pressure range for this population. Aims and objective To identify an ideal systolic blood pressure range based on optimal survival among ESRD patients on dialysis. Method A systematic search for clinical trials assessing the impact of different systolic blood pressure range on mortality among ESRD patients on hemodialysis was conducted through PubMed, EBSCOhost, Science Direct, Google Scholar and Scopus. All randomised control trials (RCTs) involving ESRD patients on hemodialysis with primary or secondary outcome of assessing the impact different systolic blood pressure range (<140 & >140mmHg) on all-cause mortality were included. The quality of reporting of the included studies was evaluated using the Jadad scale. Two researchers independently conducted eligibility assessment. Discrepancies were resolved by discussion and consultation with a third researcher when needed. Pooled relative risks (RRs) with 95% confidence intervals (CIs) were calculated. Results A total of 1787 research articles were identified during the initial search, after which six RCTs met our inclusion criteria. According to the Jadad scale, all six RCTs scored 3 points each for quality of reporting. Four RCTs employed pharmacological intervention while two RCTs assessed non-pharmacological intervention. Of the six RCTs, two studies were able to achieve a systolic blood pressure of <140mmHg at the end of trial with a RR for reduction in mortality of 0.56 (CI 95% 0.3-1.07, P 0.08). Four RCTs were able to achieve a systolic blood pressure of >140mmHg at the end of trial, with the RR for reduction of mortality of 0.72 (CI 95% 0.54-0.96, P 0.003). Overall, pooled estimates of the six RCTs suggested the reduction in systolic blood pressure statistically reduce all cause of mortality (RR 0.69%, 0.53-0.90, P 0.006) among ESRD patients on hemodialysis. Conclusion Though not statically significant, the current study identifies <140mmHg as a promising blood pressure range for optimum survival among ESRD patients on hemodialysis. However, further studies are required to establish an ideal blood pressure range among hemodialysis patients.